Bronchoscopy during the COVID-19 pandemic: effect on current practices and strategies to reduce procedure-associated transmission. (3rd June 2021) - Sampsonas, Fotios; Kakoullis, Loukas; Karampitsakos, Theodoros; Papaioannou, Ourania; Katsaras, Matthaios; Papachristodoulou, Eleni; Kyriakou, George; Bellou, Aggeliki; Tzouvelekis, Argyrios
ABSTRACT: Introduction : Bronchoscopy and related procedures have unambiguously been affected during the Corona Virus Disease 2019 (COVID-19) pandemic caused by Severe Acute Respiratory Syndrome-Corona Virus-2 (SARS COV-2). Ordinary bronchoscopy practices and lung cancer services might have changed over this pandemic and for the years to come. Areas covered : This manuscript summarizes the utility of bronchoscopy in COVID-19 patients, and the impact of the pandemic in lung cancer diagnostic services, in view of possible viral spread during these We conducted a literature review of articles published in PubMed/Medline from inception to November 5th, 2020 using relevant terms. Expert opinion : Without doubt this pandemic has changed the way bronchoscopy and related procedures are being performed. Mandatory universal personal protective equipment, pre-bronchoscopy PCR tests, dedicated protective barriers and disposable bronchoscopes might be the safest and simpler way to perform even the most complicated procedures.